Type study of Peniophora inflata (Agaricomycetes), and the introduction of the term “subicystidium” - Karasiński, Dariusz (Phytotaxa, 2014)
The type specimen of the corticioid fungus Peniophora inflata was re-examined. The term “subicystidium” (plural: subicystidia) is introduced to define basally clamped and encrusted cystidia of subicular or rhizomorphic origin. Peniophora inflata is characterized by the presence of subicystidia and hymenial lamprocystidia, a smooth, resupinate basidioma, a monomitic hyphal system, small, clavate basidia, minute ellipsoidal basidiospores negative in Melzer’s reagent and Cotton Blue, thickening hymenium and the development of rhizomorphs. The morphological similarities of Peniophora inflata with some corticioid species are discussed. Recently the generic name Sceptrulum was erected for this species. Because the introduction of the latter name lacked any discussion and clarity, the aim of this study is to provide a detailed examination of P. inflata.